Prediksi Kebangkrutan Bank - wilopo wilopo (The Indonesian Journal of Accounting Research, 2013)
Bank Indonesia controls Banks’ operations in Indonesia and their annual financial statements must be published. But several banks had poor performances, so that had to be liquidated.This study is designed to investigate whether published banks’ annual financial statements can be used to predict a possibility to bankruptcy by using CAMEL ratios and other indicators. Estimated samples were 7 banks that were liquidated and 87 banks that weren’t liquidated in 1997 with 1996’ annual fanatical statements data. Validated sampels were 16 banks that were liquidated and 70 banks weren’t liquidated in 1999with 1997’ annual financial statements data. This study used ANOVA and logit regression as statistic tools.The results of this study stated that the dominant factor of banks’ liquidation in 1997 was loosed loan to banks’ owner or group and the dominant factor of banks’ liquidation in 1999 was the high operation cost. By estimated and validated sampels test about bank bankruptcy prediction, the decision to close banks was stated for banks that had not to liquidate (error type 1). For these results, bank bankruptcy prediction should use not only CAMEL ratios, but also should use other variables as economic, politic or other factors.